Public Comprehension on Online Loan Usage (Pinjol): The Effect of Advertisement, Islamic Financial Literacy, And Lifestyle - Nabila, Syifa; Nuriyah, Aminah; Suryomurti, Wiku (Al-Infaq: Jurnal Ekonomi Islam, 2025)
This study aims to analyze the influence of online loan advertisement, Islamic financial literacy, and lifestyle on public’s comprehension and decision in online loan making. This research uses a quantitative approach with Muslim consumers in the Greater Jakarta (Jabodetabek) area as the target population. Data were collected through a questionnaire distributed via Google Form, involving 195 respondents. The data were analyzed using Structural Equation Modeling–Partial Least Square (SEM–PLS). The results show that online loan advertisement (X1) and lifestyle (X3) have a significant and positive influence on public decision in making online loans. However, Islamic financial literacy (X2) does not have significant influence on public decision in making online loans.